Gradual, but Not Sudden, Dose-Dependent Increase of ONJ Risk With Bisphosphonate Exposure: A Nationwide Cohort Study in Women With Osteoporosis - Park, Jung-Hyun; Kwoen, Min-Jeong; Lee, Jae-Ryun; Kim, Keun-Suh; Lee, Hyo-Jung; Kim, Jin-Woo; Lee, Hyejin (Frontiers in Endocrinology, 2021)
Background: Causal relationship of bisphosphonate (BP) exposure with osteonecrosis of the jaw (ONJ) has been reported, however a definite dose-dependent risk remains to be elucidated beyond current vague recommendations of 4-year oral BP for ONJ risk increase. Objective: To identify the effect of bisphosphonate cumulative dose on ONJ development in women with osteoporosis. Methods: Retrospective cohort study was designed using the National Health Insurance Service - National Health Screening database of Korea. Females over the age of 50 diagnosed with osteoporosis based on the International Classification of Diseases 10th revision (ICD-10) codes (M80, M81, and M82) with bisphosphonate prescriptions. The cumulative dose of bisphosphonate was calculated using defined daily doses (DDD) to provide an accurate BP cumulative effect on ONJ occurrence. Osteonecrosis of the jaw was identified using both ICD-10 codes and related procedure codes. The incidence rates of ONJ and hazard ratios were estimated according to the bisphosphonate cumulative dose. Results: Among 74,491 included subjects, 190 cases of ONJ were identified. The incidence rate substantially increased after BP cumulative dose over one year (25.75 for DDD<365, which increased to 53.43 for 365≤DDD<730). Compared to subjects with a cumulative dose of DDD<365, subjects with a cumulative dose of 365≤DDD<730 had 2.36-fold hazard for developing ONJ (p<0.001). Conclusion: Bisphosphonate cumulative dose of more than 1 year had an increased risk of ONJ development. Gradual, but not sudden, dose-dependent increase of ONJ risk with BP exposure needs to be considered in providing the optimal BP treatment duration.